Estudio de prefactibilidad para la instalación de una planta procesadora de cebolla (Allium cepa) deshidratada en polvo - Raffo Escuza, Gianfranco (2016)
The present investigation has analyzed the feasibility of the installation of a dehydrated onion powder plant in Peru, by determining its market, technological, economic and financial viability. Based on the results of the market research, it was determined that the target market will be United States as it is the country with the highest demand of dehydrated onion powder. By offering a product with a high quality and competitive price the present project will reach a demand of 196,58 TM in the first year and will grow up to 340,47 TM in the fifth.